Abstract This research aims to determine the use of two stay two stray method to the students’learning outcomes of mathematics of grader V SDN 12 Pontianak South. The research method used is a quasi experimental method with non-equivalent control group design. The number of research subjectis 48 students. Tool of Data collection used is in the form of essay test with six questions. The result of this research is the average of pre-test of experiment class is 25,67 while control class is 29,17. - Laraswana, Dessy Eka (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract This research aims to determine the use of two stay two stray method to the students’learning outcomes of mathematics of grader V SDN 12 Pontianak South. The research method used is a quasi experimental method with non-equivalent control group design. The number of research subjectis 48 students. Tool of Data collection used is in the form of essay test with six questions. The result of this research is the average of pre-test of experiment class is 25,67 while control class is 29,17. The average post-test of the experimental class is 79.29 and the control class is 69.25. From the result of t test, obtained tarithmeticequal to 2,62 with ttable 2.0273, it means tarithmetic> ttable concluded that there is difference of students’ learning outcome. Based on the calculation of effect size (ES), concluded that ES is 0.62. This means that the use of two stay two stray method impacts a moderate effecton the students’ learning outcome of mathematics of grader V SDN 12 Pontianak South. Keywords: Effect, Two Stay Two Stray, Learning outcome.